2014
DOI: 10.1111/acem.12540
|View full text |Cite
|
Sign up to set email alerts
|

Differential Survival for Men and Women from Out-of-hospital Cardiac Arrest Varies by Age: Results from the OPALS Study

Abstract: Background: The effect of sex on survival in out-of-hospital cardiac arrest (OHCA) is controversial. Some studies report more favorable outcomes in women, while others suggest the opposite, citing disparities in care. Whether sex predicts differential age-specific survival is still uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
90
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 50 publications
5
90
0
Order By: Relevance
“…The proportion of incidents that occurred in urban areas reflects the proportion of the Irish population that resides in urban areas. The age and gender profile of patients was very similar to other large studies of OHCA, as was the difference in median male and female ages 4 14. The proportion of patients presumed to have suffered an arrest of cardiac aetiology is similar to North American data, but high compared with other population-based studies of EMS-treated OHCA 11 14.…”
Section: Discussionsupporting
confidence: 79%
“…The proportion of incidents that occurred in urban areas reflects the proportion of the Irish population that resides in urban areas. The age and gender profile of patients was very similar to other large studies of OHCA, as was the difference in median male and female ages 4 14. The proportion of patients presumed to have suffered an arrest of cardiac aetiology is similar to North American data, but high compared with other population-based studies of EMS-treated OHCA 11 14.…”
Section: Discussionsupporting
confidence: 79%
“…This is consistent with other epidemiological data showing a greater proportion of males receive resuscitation from ambulance staff. [22] The OPALS study found that women were older than men (median age 74 versus 69 years, p < 0.01), had fewer witnessed arrests (43% vs. 49%; p < 0.01), were less likely to have shockable rhythms (24% vs. 42%; p < 0.01), and had lower rates of bystander CPR (12% vs. 17%; p < 0.01). Further research may help to explain the apparent inequality in resuscitation rates between the sexes.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the associated factors, we found that male gender, having asystole, a longer time from the cardiac arrest until the arrival of the EMS and the cardiac arrest occurring in the patient's home were significantly associated with increased mortality. There is controversy regarding gender, and it seems that this association may vary by age groups [18]. …”
Section: Discussionmentioning
confidence: 99%